Synthesis of novel nonlinear optical chromophores with enhanced electro-optic activity by introducing suitable isolation groups into the donor and bridge. Issue 26 (10th June 2019) - Liu, Fenggang; Chen, Shujie; Mo, Songmin; Qin, Gangzhi; Yu, Canwen; Zhang, Weijun; Shi, Wen-Jing; Chen, Peiling; Xu, Huajun; Fu, Mingkai
Abstract : Four nonlinear optical chromophoresA–D functionalized with different isolation groups on both the donor and bridge sections of the chromophores have been synthesized and systematically investigated. Abstract : Four nonlinear optical chromophoresA–D based on the thiolated-isophorone-derived bridge have been synthesized and systematically investigated. In particular, both the donor and bridge sections of the chromophores were functionalized with different isolation groups including tert -butyltrimethylsilane, tert -butyl(methyl)diphenylsilane, benzene ring and 1, 2, 3, 4, 5-pentafluorobenzene ring, respectively. All these four chromophores showed high thermal stabilities with decomposition temperatures above 220 °C. Most importantly, the rigid steric hindrance groups can effectively reduce the intermolecular electrostatic interactions to transform their hyperpolarizabilities into large electro-optic (EO) coefficients ( r 33 ). Polymeric thin films doped with 30 wt% chromophoresA–D have been poled to afford large r 33 values of 96, 143, 115, and 109 pm V −1 at 1.31 μm, respectively. Electro-optic performance together with density functional theory (DFT) calculations suggests that the isolation groups show different effects on the hyperpolarizability and poling efficiency of chromophores. The normalized r 33 value of chromophoreB increased to 8.36 × 10 −19 pm cc per (V molecules) indicating the largest steric hindrance group and the highest polarization efficiency. All these results provide valuable insight into the understanding of the impact of isolation groups on macroscopic EO activities of materials.